2017
DOI: 10.1186/s13068-016-0692-x
|View full text |Cite
|
Sign up to set email alerts
|

Development and implementation of rapid metabolic engineering tools for chemical and fuel production in Geobacillus thermoglucosidasius NCIMB 11955

Abstract: BackgroundThe thermophile Geobacillus thermoglucosidasius has considerable attraction as a chassis for the production of chemicals and fuels. It utilises a wide range of sugars and oligosaccharides typical of those derived from lignocellulose and grows at elevated temperatures. The latter improves the rate of feed conversion, reduces fermentation cooling costs and minimises the risks of contamination. Full exploitation of its potential has been hindered by a dearth of effective gene tools.ResultsHere we design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 55 publications
(81 reference statements)
0
56
0
Order By: Relevance
“…We have previously described the implementation of allelic exchange, gene KO systems in specifically generated pyrE mutants of Clostridium acetobutylicum (Ehsaan et al, 2016) and Clostridium difficile (Ng et al, 2013), and most recently Geobacillus thermoglucosidasius (Sheng et al, 2017). The generation of mutants by allelic exchange is facilitated by the use of replication defective, or pseudo-suicide vectors (Cartman and Minton, 2010), and the incorporation into the vector of a functional copy of a heterologous pyrE gene (encoding orotate phosphoribosyl transferase) that serves as a counter/ negative selection marker.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously described the implementation of allelic exchange, gene KO systems in specifically generated pyrE mutants of Clostridium acetobutylicum (Ehsaan et al, 2016) and Clostridium difficile (Ng et al, 2013), and most recently Geobacillus thermoglucosidasius (Sheng et al, 2017). The generation of mutants by allelic exchange is facilitated by the use of replication defective, or pseudo-suicide vectors (Cartman and Minton, 2010), and the incorporation into the vector of a functional copy of a heterologous pyrE gene (encoding orotate phosphoribosyl transferase) that serves as a counter/ negative selection marker.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of C. difficile (Ng et al, 2013) and G. thermoglucosidasius (Sheng et al, 2017) no special measures were required to achieve this, whereas in C. acetobutylicum the rational circumvention of host restriction barriers proved to be necessary by appropriate methylation of the plasmid DNA being transferred (Ehsaan et al, 2016). Here we showed that an alternative approach is possible through the isolation of a highly transformable variant of the C. pasteurianum strain DSM 525, strain CRG4111.…”
Section: Discussionmentioning
confidence: 99%
“…G. thermoglucosidasius grew relatively rapidly over the first 15 h, metabolising d-glucose and d-xylose simultaneously (Fig. 3c) [45,46]. Growth then abruptly ceased, although 74% of d-glucose and d-xylose remained.…”
Section: Characterising Growth Of Eight Microbial Species On Omsw Fibmentioning
confidence: 99%
“…1, positions 1909638 to 1910128). Single-crossover integrants and double-crossover mutants were obtained sequentially, as previously described (38), using 5-FOA at 1 mg/ml and A. woodii-specific growth medium/conditions, as described in the above section.…”
Section: Figmentioning
confidence: 99%